Peningkatan kemampuan berpikir kritis siswa SMP pada materi perpindahan kalor - Anida Chairatunnisa; Leni Marlina; Ketang Wiyono (Jurnal Penelitian Pendidikan IPA, 2023)
Critical thinking skills are rarely measured in science learning. This study aims to analyze critical thinking of junior high school students on heat transfer materials. The subjects of this study were class VII students of SMP Negeri 6 Palembang, totaling 32 seventh grade students took written tests as part of the data gathering process, which also included interviews with physics teachers. This research uses a mixed-methods strategy that combines both qualitative and quantitative data. For educational policymakers deciding on next steps, such as the choice of suitable teaching models and instructional materials, aimed at fostering the improvement of students' critical thinking abilities, understanding the profile of students' critical thinking skills serves as a valuable reference. With an average score of 36.12, the results showed that students had comparatively weak critical thinking abilities. Thus, this research can make a significant contribution to the development of effective and innovative learning methods